THE (RE)EMERGENCY DISEASES: HEALTH PROMOTION IN THE PRIMARY HEALTH CARE (Fiep Bulletin - online, 2014)
Objective: To investigate the actions of Health Promotion (HP) built on Primary Health Care through the Family Health Strategy (FHS) regarding the (re)emergence of diseases in Cajazeiras-PB. Method: It was an exploratory, descriptive and qualitative approach, performed with 12 (80%) nurses working in ESF, whose data were collected from the use of previously validated questionnaire and analyzed according to the technique of the Collective Subject Discourse. Results: Within the positions listed by the study participants, it was possible to understand that they have some understanding of the meaning of illness before (re)emerging, but what would cite these disorders are confused, citing reemerging as emerging. Nevertheless, HP has developed specific actions in cases of these diseases, especially educational activities and cross. Conclusion: (Re)emerging diseases has been of fundamental importance to the studies, at the time, was seeking the determinants by which these pathologies has been taking certain proportions in the social context, requiring interventions in the field of HP.
Keywords: Primary Health Care; Emerging and Reemerging Diseases; Health Promotion